2023
DOI: 10.3390/ijerph20020990
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of Sedentary Lifestyle in Italian Children after Solid Transplant: What Role Could Physical Activity Play in Health? It Is Time to Move

Abstract: Background: Advances in the medical–surgical field have significantly increased survival after solid organ transplantation in the pediatric population. However, these patients are predisposed to the development of long-term complications (e.g., cardiovascular disease). The therapeutic role of physical activity (PA) to counteract these complications is well known. The purpose of the study was to investigate the level of PA in a pediatric population after solid organ transplantation. Methods: In the first 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The study utilized self-reported PAQs questionnaires, which were chosen for their ease of administration and cost-effectiveness. These questionnaires have been widely used in research involving both healthy and transplanted children, demonstrating acceptable psychometric properties [23]. These questionnaires demonstrated an acceptable-to-good internal consistency, test-retest reliability, and sensitivity to detect gender differences [24,29,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study utilized self-reported PAQs questionnaires, which were chosen for their ease of administration and cost-effectiveness. These questionnaires have been widely used in research involving both healthy and transplanted children, demonstrating acceptable psychometric properties [23]. These questionnaires demonstrated an acceptable-to-good internal consistency, test-retest reliability, and sensitivity to detect gender differences [24,29,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of sufficient exercise practice is detrimental to the physical, mental health, and quality of life of transplant recipients while there is robust evidence that exercise can work as a medicine for the health not only of transplanted subjects but also for a variety of neurological, psychiatric, cardiometabolic, respiratory and musculoskeletal pathologies [22]. However, current post-transplant approaches are insufficient to fully address the right amount of physical activity for these patients, and physical exercise is not part of the post-transplant long-term therapy protocols [23]. Therefore, the present study aimed to compare the lifestyle of two groups of young patients.…”
Section: Introductionmentioning
confidence: 99%